Effect of Deposition Thickness on Critical Shear Stress for Incipient Motion of Sediments - Charles Hin Joo, Bong; F.J., Putuhena; T.L., Lau; A. Ab., Ghani (2015)
The current understanding on how sediment deposition thickness could affect the incipient motion of sediment is still lacking in the literature. Few existing literature suggested that the current equation for incipient motion in rigid boundary channel with limited sediment depth become less accurate as the sediment bed thickness increased. The current study highlights the effect of sediment deposits thickness on critical shear stress of sediment in rigid rectangular channel. Results of experimental work on incipient motion were used to establish the effect of sediment deposits thickness on critical shear stress. Findings from the analysis shows that sediment deposits thickness has effect on the critical shear stress at low sediment bed thickness and the effect will reduce with the increased in sediment bed thickness. A new equation for predicting critical shear stress was proposed by incorporating the sediment deposits thickness and appears to be more consistent and was not much affected by the sediment deposits thickness as compares to the existing rigid boundary equations. The new equation is an attempt toward unifying the equations for both rigid boundary and loose boundary conditions.